The Development of VGL Catering Booking System: VGL Cate using object-oriented approach - Letchumanan, Vaani; Mat Nawi, Rosmamalmi (Applied Information Technology And Computer Science, 2024)
The VGL Catering Booking System addresses the need for a systematic booking management system for VGL Catering. This project aims to design and develop a comprehensive catering booking management system for VGL Catering, integrating a more systematic method like the E-Catering system. The system will be presented as a new branded online platform dedicated to handling bookings for VGL Catering. The objectives include implementing login, food ordering, date reservation, and data management modules, ensuring system functionality and usability. The waterfall model is employed as the methodology for developing the system. The main problem this system solves is the difficulty faced by customers in checking VGL Catering’s availability due to the absence of a proper booking system. Additionally, management faces challenges in organizing and managing catering bookings effectively. The system will enable customers to reserve dates in advance by paying a deposit via online payment, even without placing a food order. The proposed system, VGL Cate, is designed based on an object-oriented approach, with the main feature being the booking system. By utilizing the VGL Cate system, customers can easily make decisions when booking food and catering services.